Chemical profiling of African leaves (Vernonia amygdalina Delile) and Kenikir leaves (Cosmos caudatus Kunth) extracts using Thin Layer Chromatography (TLC) - Relin Yesika; Meridha Mutiara A; Nurwahidatul Arifa; Arif Ferdian; Miming Andika; Yahdian Rasyadi; Nana Liana; Erdanela Setiawati (JURNAL FARMASI DAN MAKANAN, 2023)
African leaves (Vernonia amygdalina Delile) and kenikir leaves (Cosmos caudatus Kunth) are plants that belong to the asteraceae family. Members of asteraceae have been used in food and medicine for centuries. This study aims to determine the secondary metabolite compounds contained in African leaves extracts and kenikir leaves through phytochemical screening using Thin-layer chromatography (TLC) method detected using UV 254nm and UV 366 nm light, as well as spot revealers that match the chemical group. The results of phytochemical screening using KLT show that African leaves contain flavonoids, terpenoids. And kenikir leaf extract is positive for steroids and flavonoids, one of them which is isocuesitrin.